Cloud Computing Environments Which Can Be Used in Health Education - Buber, Mustafa; Sucu, Fadime; Bulut, Ismail; Kursun, Ramazan (International Journal of Intelligent Systems and Applications in Engineering, 2015)
At the present time, it is known that cloud computing technologies began to be used widely in information technology. The purpose of this study is to provide information about cloud technologies that can be used in health education. For this purpose,firstly as sample of the learning content management system, Edmodo has been introduced. Hapyak Interactive Video Creation Platform which can be used for creating interactive video to enrich the learning environment that will be submitted with Edmodo, Bubbl.Us which can be benefited from summarizing the discussed and Socrative platforms which enable concept maps application and online test creation have been introduced.